PERAN CUSTOMER RELATIONSHIP MANAGEMENT DALAM MENINGKATKAN RETENSI PELANGGAN DI ANNAHL TRAVEL SURABAYA - Eka Rahma Sania; Afiyah (Jurnal Manajemen dan Pemasaran, 2025)
This study discusses the role of customer relationship management in increasing customer retention at annahl travel surabaya. In the increasingly competitive travel industry, CRM plays an important role in building long- term relationships with customers through structured communication, loyalty programs, and customer data management. This study uses a qualitative approach with data collection techniques in the form of in-depth interviews, observation, and documentation. The results of the study show that CRM at An Nahl Travel is not only applied during the departure of worship, but also afterwards through personal follow-up, special offers, and ongoing communication through digital platforms. Old customers are prioritized through loyalty programs and transparent services. CRM has been proven to contribute greatly to customer satisfaction and loyalty, despite challenges such as untidy data and limited follow-up time. In the future, An Nahl plans to optimize the CRM system with modern applications and more structured loyalty programs.